Comparison of artemisinin suppositories, intramuscular artesunate and intravenous quinine for the treatment of severe childhood malaria. - Cao, X; Bethell, D; Pham, T; Ta, T; Tran, T; Nguyen, T; Pham, T; Nguyen, T; Day, N; White, N (1997)
Severe malaria remains a major cause of mortality and morbidity for children living in many tropical regions. With the emergence of strains of Plasmodium falciparum resistant to both chloroquine and quinine, alternative antimalarial agents are required. The artemisinin group of compounds are rapidly effective in severe disease when given by intramuscular or intravenous injection. However, these routes of administration are not always available in rural areas. In an open, randomized comparison 109 Vietnamese children, aged between 3 months and 14 years, with severe P.falciparum malaria, were allocated at random to receive artemisinin suppositories followed by mefloquine (n = 37), intramuscular artesunate followed by mefloquine (n = 37), or intravenous quinine followed by pyrimethamine/sulfadoxine (n = 35). There were 9 deaths: 2 artemisinin, 4 artesunate and 5 quinine-treated children. There was no difference in fever clearance time, coma recovery, or length of hospital stay among the 3 groups. However, parasite clearance times were significantly faster in artemisinin and artesunate-treated patients than in those who received quinine (P < 0.0001). Both artemisinin and artesunate were very well tolerated, but children receiving these drugs had lower peripheral reticulocyte counts by day 5 of treatment than those in the quinine group (P = 0.011). No other adverse effect or toxicity was found. There was no treatment failure in these 2 groups, but 4 patients in the quinine group failed to clear their parasites within 7 d of starting treatment and required alternative antimalarial therapy. Artemisinin suppositories are easy to administer, cheap, and very effective for treating children with severe malaria. In rural areas where medical facilities are lacking these drugs will allow antimalarial therapy to be instituted earlier in the course of the disease and may therefore save lives.